2018
DOI: 10.1002/ajp.22933
|View full text |Cite
|
Sign up to set email alerts
|

Diel and infradian (7‐day) activity rhythms in Mexican spider monkeys (Ateles geoffroyi) kept with and without visitor contact

Abstract: Diel activity rhythms in mammals are regulated by an endogenous (circadian) timing system which is synchronized by environmental 24-hr periodicities called zeitgebers.Additional direct responses to stochastic environmental factors ensure the fine-tuning to the actual situation and may mask the circadian time course. Following an observational study on behavioral effects of visitor activities in a group of spider monkeys (Ateles geoffroyi) kept free-ranging on a small island of Lake Catemaco, Veracruz, Mexico, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Other studies found interspecific differences in the way primates allocate time to different activities: the mantled howler monkey, A. palliata, spent a considerable amount of time resting, feeding, and moving around (Muñoz et al 2001); Guatemalan black howlers (A. pigra), rested more frequently in highquality habitats (Rangel-Negrín et al 2018); separately, the periods of rest and activity of spider monkeys (A. geoffroyi), were mainly driven by light-darkness periods and environmental factors such as temperature, precipitation, and humidity (Muñoz-Delgado et al 2004). In this last species, in Catemaco, Veracruz, Muñoz-Delgado et al (2014) studied the impact of housing conditions and season on the daily timing and pattern, and Muñoz-Delgado et al (2018), recorded that these primates respond to visitor (tourist) activity since it modified their normally pronounced bimodal diel activity pattern and developed a superimposed infradian activity rhythm peaking on Saturday and Sunday.…”
Section: Conservation and Behaviormentioning
confidence: 99%
“…Other studies found interspecific differences in the way primates allocate time to different activities: the mantled howler monkey, A. palliata, spent a considerable amount of time resting, feeding, and moving around (Muñoz et al 2001); Guatemalan black howlers (A. pigra), rested more frequently in highquality habitats (Rangel-Negrín et al 2018); separately, the periods of rest and activity of spider monkeys (A. geoffroyi), were mainly driven by light-darkness periods and environmental factors such as temperature, precipitation, and humidity (Muñoz-Delgado et al 2004). In this last species, in Catemaco, Veracruz, Muñoz-Delgado et al (2014) studied the impact of housing conditions and season on the daily timing and pattern, and Muñoz-Delgado et al (2018), recorded that these primates respond to visitor (tourist) activity since it modified their normally pronounced bimodal diel activity pattern and developed a superimposed infradian activity rhythm peaking on Saturday and Sunday.…”
Section: Conservation and Behaviormentioning
confidence: 99%
“…">We expected that smaller distances to plantations would trigger proboscis monkeys' activity (positively masking activity patterns). Nights spent near plantations may be associated with higher human density, which could disrupt sleep or cause increased vigilance in proboscis monkeys (Gaynor et al, 2018; Leasor & Macgregor, 2004; Muñoz‐Delgado et al, 2018; Tagg et al, 2018). Proboscis monkeys avoid sleeping sites near high human activity, which could indicate increased stress in the presence of humans and, thus, presence of nocturnal activity around plantations (Boonratana, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nights spent near plantations may be associated with higher human density, which could disrupt sleep or cause increased vigilance in proboscis monkeys (Gaynor et al, 2018;Leasor & Macgregor, 2004;Muñoz-Delgado et al, 2018;Tagg et al, 2018).…”
Section: Introductionmentioning
confidence: 99%